Biodiversity Between Integration and Application Scientific Research Resulting in Management for Use Sustainable and Conservation (Revista Brasileira Multidisciplinar, 2010)
Brazil's biodiversity is recognized as one of the greatest in the world. However, accelerating rates of environmental disruption, with biodiversity loss within the Brazilian biomes, have the potential to negatively affect the range of wild species that serve as extractive products, to be modified through domestication or through selective breeding and hybridization as new sources of food and other uses, including pharmaceutical goods. In addition to its intrinsic value, that is, nature working as it is, biodiversity plays an important role in ecosystem services in the maintenance of natural ecological processes: air purification, water, food, medicines, cosmetics and essential products for human well-being. With the advance of Brazilian scientific research, particularly biotechnology, it is possible to provide new products, to supply market demand for ornamental species and other extractive products, food, medicines, cosmetics and other uses. Here I analyze different case studies to show the role of biodiversity in new findings from scientific research and identify potential economic uses of some species.
Keywords: Biological diversity; biotechnology; conservation of nature; ecosystem services; Extractivistic products.